2015
DOI: 10.1007/s00198-015-3340-6
|View full text |Cite
|
Sign up to set email alerts
|

Greater access to fast-food outlets is associated with poorer bone health in young children

Abstract: The neighbourhood food environment that pregnant mothers and young children are exposed may affect bone development during early childhood. If confirmed in future studies, action to reduce access to fast-food outlets could have benefits for childhood development and long-term bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Since physical inactivity is associated with reduced muscular loading, it may theoretically also lead to reductions in bone mass. Comparable results that highlighted negative effects of an unhealthy diet on the musculoskeletal system have previously been reported [ 52 ]. Regular fast food intake was also associated with increases in body weight in these children.…”
Section: Discussionsupporting
confidence: 71%
“…Since physical inactivity is associated with reduced muscular loading, it may theoretically also lead to reductions in bone mass. Comparable results that highlighted negative effects of an unhealthy diet on the musculoskeletal system have previously been reported [ 52 ]. Regular fast food intake was also associated with increases in body weight in these children.…”
Section: Discussionsupporting
confidence: 71%
“…Financial constraints on local councils could hinder action, however, building evidence from natural experiments and advocating for central government support could enable councils to take action [ 50 ]. Further intervention research to explore the effects of increasing access to healthy specialty stores such as fruit and vegetables stores is needed to improve understanding of their potential beneficial effects on health [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that children with one or more greengrocers or supermarkets around their home had lower fizzy drink intake and percentage body fat than children with no access to these outlets ( 41 ) . Another study showed that having greater access to healthy specialty stores in the home neighbourhood was associated with better bone health in children aged 4 years ( 42 ) . Furthermore, a large national study observed that higher counts of healthy specialty stores, supermarkets and cafés in the home neighbourhood related to a lower prevalence of overweight and obesity among young children (aged 4–5 years) but not older children (aged 10–11 years) ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%